2021
DOI: 10.1007/s10493-021-00678-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of B-azolemiteacrylic on life-history traits and demographic parameters of two-spotted spider mite, Tetranychus urticae (Acari: Tetranychidae)

Abstract: The present study was conducted to evaluate sublethal effects of B-azolemiteacrylic on the two-spotted spider mite, Tetranychus urticae Koch (Acari: Tetranychidae). Female adults of T. urticae were exposed to LC10 and LC30 of the acaricide, and the effects on treated females and their offspring were evaluated. The results showed that the fecundity of F0 female adults treated with LC10 and LC30 of B-azolemiteacrylic was reduced by 30.9 and 39.2%, respectively. Longevity and oviposition period of the females wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Although the LD-HN population had a moderate level of resistance to B-azolemiteacrylic (RF = 12.80), the other four T. urticae populations remained sensitive to B-azolemiteacrylic. Based on the current results and those of a previous study [34], which showed that the use of B-azolemiteacrylic inhibited the developmental rate of T. urticae and did not readily select for resistance, we suggest that B-azolemiteacrylic can still be used to control T. urticae in Hainan.…”
Section: Alternative Use Of Novel Pesticides For T Urticae Controlsupporting
confidence: 67%
“…Although the LD-HN population had a moderate level of resistance to B-azolemiteacrylic (RF = 12.80), the other four T. urticae populations remained sensitive to B-azolemiteacrylic. Based on the current results and those of a previous study [34], which showed that the use of B-azolemiteacrylic inhibited the developmental rate of T. urticae and did not readily select for resistance, we suggest that B-azolemiteacrylic can still be used to control T. urticae in Hainan.…”
Section: Alternative Use Of Novel Pesticides For T Urticae Controlsupporting
confidence: 67%
“…The two-spotted spider mite, Tetranychus urticae (Koch), represents a pervasive global threat to agricultural productivity [1], wreaking havoc on crops, fruit trees, and vegetables [2][3][4], particularly in greenhouse and controlled environment agriculture settings [5]. These minuscule pests take up residence on the undersides of plant leaves, spinning intricate webs to create microhabitats that shield them from environmental stressors, ward off predators, enable pheromonal communication, and facilitate dispersion [6].…”
Section: Introductionmentioning
confidence: 99%
“…The two-spotted spider mite Tetranychus urticae represents one of the key pest mites around the world and has a high capacity to adapt to a wide range of hosts. It can feed on many economic crops and ornamental plants, which covers over 1275 plant species from 70 genera [ 1 , 2 , 3 ]. T. urticae uses its mouthparts to penetrate host cells and ingest cell contents that lead to a decreased transpiration and photosynthesis activity decrease and delayed development of plants [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%